Evaluating the potential of IASI ozone observations to constrain simulated surface ozone concentrations - M. Beekmann; A. Ung; A. Coman; A. Boynard; G. Dufour; C. Keim; M. Eremenko; C. Schmechtig; L. Hamaoui; G. Foret (Atmospheric Chemistry and Physics, 2009)
A tracer study has been performed for two summers in 2003 and 2004 with a regional chemistry-transport model in order to evaluate the potential constraint that tropospheric ozone observations from nadir viewing infrared sounders like IASI or TES exert on modelled near surface ozone. As these instruments show high sensitivity in the free troposphere, but low sensitivity at ground, it is important to know how much of the information gained in the free troposphere is transferred to ground through vertical transport processes. Within the European model domain, and within a time span of 4 days, only ozone like tracers initialised in vertical layers above 500 hPa are transported to the surface. For a tracer initialised between 800 and 700 hPa, seven percent reaches the surface within one to three days, on the average over the European model domain but more than double over the Mediterranean Sea. For this region, trajectory analysis shows that this is related to strong subsident transport. These results are confirmed by a second tracer study taking into account averaging kernels related to IASI retrievals, indicating the potential of these measurements to efficiently constrain surface ozone values.